P-184 St Clare Hospice Bereavement Journey Project: A cross-hospice project for an integral pathway. (19th November 2022) - Abbas, Syed Qamar; Burrows, Justine; Dhami, Sushma; Macdonald, Gill; Taylor, Denise; Evans, Sophie; Day, Rebecca
Abstract : Background: Getting communications to family members/carers right post a bereavement is important. At St Clare Hospice, it was recognised that there were inconsistencies in communication processes. A cross-organisational project team implemented a new co-ordinated communications strategy. The team included Fundraising, Patient & Family Support, Marketing & Communications and the Quality & Governance Lead. Aims: To improve the experience of families/carers after a death; normalise the grieving process, and widely communicate the hospice bereavement services. To combat loneliness, feelings of isolation and unsurety about where to turn. To ensure the secure collation and processing of family/carer data. To provide a seamless journey from a person's experience of end of life care, through their own bereavement support, and on to a longer term relationship with the hospice as a supporter. Methods: Project team meeting regularly. The transfer of family/carer data to a database (Raiser's Edge) to achieve fully rounded and secure records of all communications to bereaved people. Audit undertaken to determine the best time to send bereavement information. Creating a Post Bereavement Journey Communications Planner – including bereavement services information, and appropriate in-memory fundraising. Results: Introduction of a robust process to transfer family/carer data from SystmOne to Raiser's Edge. New handwritten condolence cards – mailed out within a week of a death. Creation of a 'Guidance and support after a death' booklet. 4 and 16 weeks bereavement packs. Living with Grief workshop and remembrance service. Conclusion: The Bereavement Journey Project has been received well within the hospice and by family/carers. An audit is planned to review feedback on this project. Family/carers will be invited to Bereavement Connection days so they engage with the hospice on long term supportive plans.